ANALISIS PENGARUH BIAYA OPERASIONAL PADA PERUSAHAAN PENERBANGAN NASIONAL - Biantara, Dheny (School of Accountancy, University of Agung Podomoro, 2017)
Summarized Indonesian airline executive views on the reason for the cost problem in mayor airline andon the potential areas and measures of cost reduction in airline operation. Present an introductionsurvey where 3 executives from 3 Indonesian airlines were respondent. In the executive opinion the costproblem in mayor Indonesian airline is primarily due to fuel and oil pricing and money currency. Of thevarious function in airline maintenance was seen as least cost efficiency, whereas flight operation wasseen as an area with most potential for cost reduction. Indonesian airline had made route and fleetchanges after the beginning of 2011 to reduce cost, concludes from the analisys result havingprivatization would be an important step towards more efficient airline operation. Flexibility fromIndonesian airline regulatory would be very much welcome and the value chain concept to improveIndonesian airline having competitive advantage and cost leadership differentiation.